Pengaruh Profitabilitas, Ukuran Perusahaan, dan Tingkat Pertumbuhan Perusahaan Terhadap Struktur Modal pada Perusahaan Sektor Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2020 - Anggi Pratiwi Sitorus; Rolita Christina Purba; Budianto (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
This study aims to find the effect of profitability, corporate governance, and tax avoidance on firm value in manufacturing companies listed on the Indonesia Stock Exchange in 2017-2020 partially and simultaneously. The population of this study was 65 companies. The sampling method used is purposive sampling method, so that 10 companies were obtained as samples for 4 years of observation with 40 observation samples. The research data was obtained from financial reports from sample companies which were downloaded through the IDX website, namely www.idx.co.id and the official websites of each company. The data analysis technique used is multiple linear regression analysis using SPSS 25. The results showed that the profitability variable had a positive and significant effect on capital structure. Firm size has a significant negative effect on capital structure and company growth rate variable has a positive and insignificant effect on capital structure. Based on the simultaneous test (F test) the variables of profitability, company size and growth rate simultaneously affect the capital structure.